2010
DOI: 10.1111/j.1365-2710.2009.01069.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of CYP2C19 genetic polymorphisms in a korean population using a simultaneous multiplex pyrosequencing method to simultaneously detect the CYP2C19*2, CYP2C19*3, and CYP2C19*17 alleles

Abstract: The multiplex pyrosequencing method to detect CYP2C19*2, CYP2C19*3, and CYP2C19*17 concurrently, seems to be a rapid and reliable genotyping method for the detection of important CYP2C19 genetic polymorphisms. Similar to studies conducted on other Asian populations, this study reported that in the Korean population tested, the CYP2C19*2 and CYP2C19*3 alleles were relatively frequently found, whereas the frequency of CYP2C19*17 was very low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 22 publications
5
26
0
3
Order By: Relevance
“…9 The allele frequencies of CYP2C19*1, *2, and *3 from 271 Korean healthy and unrelated subjects are reported to be 60.0%, 28.4%, and 10.1%, respectively. 20 In addition, the phenotype proportions of CYP2C19 were 35.7% for EMs (*1/*1), 47.2% for IMs (*1/*2 and *1/*3), and 14.0% for PMs (*2/*2, *3/*3, and *2/*3). 20 In our institution, we investigated the CYP2C19 genotypes from 1010 Korean patients referred for CYP2C19 genotyping.…”
Section: Discussionmentioning
confidence: 98%
“…9 The allele frequencies of CYP2C19*1, *2, and *3 from 271 Korean healthy and unrelated subjects are reported to be 60.0%, 28.4%, and 10.1%, respectively. 20 In addition, the phenotype proportions of CYP2C19 were 35.7% for EMs (*1/*1), 47.2% for IMs (*1/*2 and *1/*3), and 14.0% for PMs (*2/*2, *3/*3, and *2/*3). 20 In our institution, we investigated the CYP2C19 genotypes from 1010 Korean patients referred for CYP2C19 genotyping.…”
Section: Discussionmentioning
confidence: 98%
“…따라서 국내에서는 인체 간세포를 이용한 in vitro 약물평가가 필요한 경우 미국 및 유럽 등지의 간세포 공급업 체들로부터 동결된 간세포를 수입하여 사용하고 있는 실정 이다 [4]. 여러 보고에 따르면, 한국인에서 자주 나타나는 약물대사 효소 변이가 있고 그로 인해 약물에 대한 반응이 다르게 나 타난다고 한다 [5,6]. 이처럼 인종간에 따라 간 대사의 차이 가 크기 때문에 미국 및 유럽의 간세포 공급업체에서는 간 기증자의 인종을 적시하고 있다.…”
Section: 서론 신약 개발이 증가함에 따라 약물대사 및 수송체 (Transporter)unclassified
“…하지만, 국내의 경우 전체 간이식의 대부분이 생체기증 간이식이며 [7], 기증된 뇌사자의 간은 대부분 이식에 사용되고 있어서 인체 간세포 분리를 위한 간 조직 원료로 활용될 수 있는 경 우는 매우 드물다. 또한 약물대사에 관여하는 효소의 유전적 다양성은 인종간 차이뿐 아니라 개인간에도 차이를 보이기 때문에 [5,6] 여러 사람의 간세포를 하나로 군집시킨 형태로 동결보존하여 약물대사에 있어 개인 간 차이에 따른 오차를 줄이는 방식으로 약물 대사 연구에 사용하기도 한다 [8]. 인체 간으로부터 간세포를 분리하는 방법은, 전간 (whole liver)의 경우 간문맥 등의 혈관을 통해 간 조직 전체를 EDTA 용액과 콜라겐분해효소용액을 순차적으로 관류하는 방식이 일반적이다 [9].…”
Section: 서론 신약 개발이 증가함에 따라 약물대사 및 수송체 (Transporter)unclassified
“…[14] In case of CYP2C19*17, it was identified in several Korean studies. [15,16] but there was no report in Vietnamese population. The CYP2D6 exists as a small proportion of drug metabolizing enzymes in liver (about 2%), but it is very important on drug metabolism (20-25% of total drugs in market).…”
Section: Introductionmentioning
confidence: 98%
“…For Korean population, referred data were gathered in CYP2C9 reported by Lee et al, [27] CYP2C19 reported by Kim et al, [16] CYP2D6 reported by Lee et al, [28] CYP3A4 reported by Lee et al, [21] and CYP3A5 reported by Yoo et al [29] For Vietnamese population, referred data were gathered in CYP2C9 reported by Lee et al, [12] CY-P2C19 reported by Lee et al, [30] CYP2D6 reported by Kim et al, [25] CYP3A4 and CYP3A5 reported by Veiga et al [31] …”
Section: Data Collection From Previous Studiesmentioning
confidence: 99%